Power relations in social media discourse: Dialogization and monologization on corporate Facebook pages. (June 2016) - Lillqvist, Ella; Louhiala-Salminen, Leena; Kankaanranta, Anne
Abstract: Social media have inspired optimistic claims of empowerment of consumers vis-à-vis corporations; however, an ongoing commercialization of online contexts may compromise such equalization. This study takes a critical discourse studies perspective and contributes to a nuanced understanding of discursive power relations between companies and consumers on social media by analyzing the possibilities that corporate Facebook pages provide for consumer participation and criticism and for corporate manipulation of discourse. To do this, the study draws from Bakhtin׳s view of dialogue to shed light on contextual and discoursal features which operate to either promote or silence voices. We show how the features of Facebook provide methods for "monologization" making the discourse appear participative while still controlling which voices are heard. Highlights: Examines power relations between companies and consumers in social media. Combines a critical discourse studies perspective with a Bakhtinian view of dialogue. Shows how divergent voices are promoted and silenced on corporate Facebook pages. The discourse is made appear participative while controlling which voices are heard. Facebook itself plays a key role in skewing discursive power relations.